Le immagini delle “cattedrali del consumo” in alcuni romanzi italiani contemporanei - Szymura, Magdalena (Romanica Silesiana)
In his Enchanting a Disenchanted World. Revolutionizing the Means of Consumption George Ritzer depicts the analogies between religious and consumer behaviour observed in shopping malls and superstores, franchises and fast food restaurants, on cruise lines, in theme parks and restaurants. Ritzer calls those locations the cathedrals of consumerism. According to sociologists, a sacred, ritual character of commodities consumption can be compared to the dynamics of religious acts of worship, especially in shopping malls. In Italian literature, the means and landscapes of consumption provide meaningful backgrounds for the writers to expose the influence of consumerism on social life and interpersonal relationships. Key words: consumerism, cathedrals of consumerism, religious ritual, social relations, contemporary Italian novel